Numerical simulation of pin squeeze casting process for cycle time and cast property prediction. (11th May 2010) - Quadrini, F.; Santo, L.; Tagliaferri, V.; Olimpi, A.
A new casting process was defined to fabricate small connecting rods generally produced by die casting. An additional pressure was applied by means of cylindrical pins during the alloy solidification to improve local mechanical properties. The pins were inserted in the fixed semi-mould and moved by high pressure nitrogen. Connecting rods were fabricated at different squeeze pressures, squeeze times and delay time between the end of the filling stage and the beginning of the pin squeezing. Indentation tests were carried out to measure the effect of the squeezing on the mechanical properties of the cast alloy and a significant improvement was measured. A finite element (FE) model was proposed to simulate the cooling stage of the connecting rod with and without the squeeze pressure. The model was able to predict the modification in mechanical property distribution due to the squeeze pressure and to estimate the reduction in cycle time.